Pengaruh Content Marketing, Social Media Marketing, dan Electronic Word Of Mouth Terhadap Keputusan Memilih Universitas Pamulang pada Calon Mahasiswa Baru (Studi pada Calon Mahasiswa Baru Universitas Pamulang) - Rahmat Firmansyah; Ilham Sanusi; Muhammad Fany Panerus; Arief Saepudin; Danil Fadilah; Rifkhan Rifkhan (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study examines the effect of Content Marketing (X1), Social Media Marketing (X2), and Electronic Word of Mouth (X3) on the decision of prospective new students to choose Universitas Pamulang (Y). A quantitative explanatory approach was used with 60 respondents selected through purposive sampling, analyzed using IBM SPSS. All questionnaire items were valid (Pearson correlation 0.670-0.892, above the r-table value of 0.196) and reliable (Cronbach's Alpha 0.723-0.827). The classical assumption tests confirmed that the data were normally distributed, free of multicollinearity, free of heteroscedasticity, and free of autocorrelation. The multiple linear regression equation obtained is Y = 0.771 + 0.174X1 + 0.131X2 + 0.419X3. Partial tests (t-test) show that Content Marketing (t = 1.571, p = 0.122) and Social Media Marketing (t = 1.795, p = 0.078) do not significantly affect college choice decisions, while Electronic Word of Mouth (t = 3.856, p < 0.001) has a positive and significant effect and emerges as the most dominant predictor. Simultaneously (F-test), F = 27.881 (p < 0.001), confirming that the three variables jointly influence the decision. The coefficient of determination R2 = 0.599 (Adjusted R2 = 0.577) indicates that 59.9 percent of the variance in college choice decisions is explained by the three variables, while the remaining 40.1 percent is explained by other factors outside the model.